2011
DOI: 10.1088/0953-2048/24/7/075002
|View full text |Cite
|
Sign up to set email alerts
|

EnhancedJcBproperties of MgB2tapes by yttrium acetate doping

Abstract: We report the effect of yttrium acetate addition on in situ powder-in-tube processed MgB 2 /Fe tapes. The amount of yttrium acetate was varied from 0 to 20 wt% and sintering was performed at 700-850 • C for 1 h in a flowing Ar atmosphere. We found that a significant J c -B enhancement was easily achieved in high field by yttrium acetate doping. At 4.2 K, the transport J c for the best yttrium-acetate-added tapes (10 wt%) reached almost 10 4 A cm −2 at 12 T. The improvement of J c performance in the yttrium-ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…A shift of the peak towards higher field could be seen after SiC doping, and another slight shift could be seen after Y 2 O 3 doping. It means that a pinning force was provided by YB 4 besides C doping, which almost agrees with the analysis in [26]. In addition, minor flux jumps caused by low stability of magnetic flux revealed at 0 ∼ 0.5 T, which were almost the same as those appearing in bulk at 2 K [27], have been shown in Fig.…”
Section: ) Figures 3(a) 3(b) and 3(c)supporting
confidence: 84%
“…A shift of the peak towards higher field could be seen after SiC doping, and another slight shift could be seen after Y 2 O 3 doping. It means that a pinning force was provided by YB 4 besides C doping, which almost agrees with the analysis in [26]. In addition, minor flux jumps caused by low stability of magnetic flux revealed at 0 ∼ 0.5 T, which were almost the same as those appearing in bulk at 2 K [27], have been shown in Fig.…”
Section: ) Figures 3(a) 3(b) and 3(c)supporting
confidence: 84%
“…The quite strong flux pinning in R750 shows up in the low-field thermomagnetic instability appearing already at 15 K (figure 4), whereas in the undoped MgB 2 samples such instability appears only below 10 K [16,36]. The J cm data in figure 4 seem to confirm the conjecture (based on extrapolation of J c results in figure 3 to low fields) that the zero-field J c of our samples is either unaffected or enhanced by co-doping, which contrasts sharply with what was observed upon co-doping MgB 2 with yttrium acetate [37] and iron(II)lactate [18].…”
Section: Resultssupporting
confidence: 62%
“…When the concentration of yttrium acetate is 0.0035 mol/L, the ability to promote cell growth is the strongest, and the biocompatibility is the best.It proves the addition of Y element can promote cell growth, and this is consistent with the research results of Li. 23 .…”
Section: Cck-8 Cytotoxicity Results and Discussionmentioning
confidence: 99%
“…[20][21] Xing et al 22 added yttrium to the A50 magnesium alloy, thereby improving the microscopic grain structure of the magnesium alloy and optimizing the mechanical properties. Wang et al 23 incorporated yttrium acetate into MgB 2 magnesium alloys to significantly improve the optoelectronic properties of magnesium alloys. Liu 24 and others found that during micro-arc oxidation, rare earth elements in the electrolyte can enter the ceramic layer with the oxidation process, thereby improving the corrosion resistance of magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%